Derisking delta-oriented value chains in Cambodia, Vietnam and Myanmar: Scoping study on key production systems and value chains - Gonsalves, Julian Francis; Carandang, Arvin; Verallo III, Jose Roy; Barbon, Wilson John (2022)
This scoping study report provides critical input to AMD-Focus Area 3 for a digital landscape and users’ needs assessment to be conducted in Vietnam, Cambodia, and Myanmar by prioritizing the key production systems and value chains where AMD-WP3 will continue or build its work in the next three years. The scoping study team, led by the International Institute of Rural Reconstruction (IIRR) implemented a systematic desk review and initial screening and prioritization followed by a validation process in each country to finalize the priority production systems.